PGM3 insufficiency: a glycosylation disorder causing a notable T cell defect - Yang, Linlin; Zerbato, Barbara; Pessina, Alex; Brambilla, Luca; Andreani, Virginia; Frey-Jakobs, Stefanie; Fliegauf, Manfred; Barbouche, Mohamed-Ridha; Zhang, Qiaoxia; Chiaradonna, Ferdinando; Proietti, Michele; Du, Xin; et al. (Frontiers in Immunology, 2024)
BackgroundHypomorphic mutations in the phosphoacetylglucosamine mutase 3 (PGM3) gene cause a glycosylation disorder that leads to immunodeficiency. It is often associated with recurrent infections and atopy. The exact etiology of this condition remains unclear.ObjectiveThis study aimed to characterize the phenotypes and immunological features associated with PGM3 insufficiency and investigate potential disease mechanisms.MethodsA systematic review of 44 published cases of PGM3 variants was performed, followed by T-cell phenotyping of two patients with PGM3 variants. A genotype-phenotypic severity study was conducted by comparing the residual PGM3 expression of the 12 reconstituted variants in human B cells. A PGM3 inhibitor was used to assess its effect on CD4+ T cell proliferation and differentiation.ResultsPatients with PGM3 variants frequently presented with recurrent infections and atopy, accompanied by reduced naïve CD4+ T cell counts. A genotype–phenotype study showed that low levels of residual PGM3 expression are correlated with disease severity. Notably, inhibition of PGM3 activity impaired TCR-mediated CD4+ T cell proliferation and the synthesis of UDP-GlcNAc, complex N-glycans, O-GlcNAc, glycolytic stress, and mitochondrial respiration during proliferation in a dose-dependent manner. Partial loss of PGM3 activity was observed to preferentially enhance Th1 and Th2 differentiation, while attenuating Th17 and Treg differentiation, consistent with clinical observations.ConclusionPGM3 is a critical regulator of CD4+ T-cell proliferation and differentiation. These findings provide new insights into the diverse clinical manifestations and therapeutic development of PGM3 deficiency.